2008
DOI: 10.2460/ajvr.69.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharmacodynamic variables following oral versus transdermal administration of atenolol to healthy cats

Abstract: Oral administration of atenolol at a median dose of 1.1 mg/kg every 12 hours (range, 0.8 to 1.5 mg/kg) in cats induced effective plasma concentrations at 2 hours after treatment in most cats. Transdermal administration provided lower and inconsistent plasma atenolol concentrations. Further studies are needed to find an effective formulation and dosing scheme for transdermal administration of atenolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…[3][4][5][6][7][8] The transdermal application of drugs has become popular in feline medicine, as cats can be difficult to consistently medicate PO. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The vehicle carrier affects the absorption of drugs across the skin by having a primary role in determining the partition coefficient for the drug and can also alter the properties of the skin. 28 The correct vehicle is required for each drug for maximum transdermal penetration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] The transdermal application of drugs has become popular in feline medicine, as cats can be difficult to consistently medicate PO. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The vehicle carrier affects the absorption of drugs across the skin by having a primary role in determining the partition coefficient for the drug and can also alter the properties of the skin. 28 The correct vehicle is required for each drug for maximum transdermal penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, many compounding pharmacies have started formulating drugs into gels, which are applied to the inner side of the cat's ear and are thought to be absorbed through the skin for systemic action. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Not all drugs are suitable for transdermal penetration and only a few drugs have been studied in cats to determine whether they reach therapeutic concentrations after absorption by this route. [21][22][23]26,27,30,31 There are several factors that affect the transdermal delivery of drugs.…”
mentioning
confidence: 99%
“…MacGregor et al 35 and Quinones et al 36 evaluated the pharmacokinetic and pharmacodynamic effects of orally administered atenolol in healthy cats. These studies revealed that atenolol induces a time-dependent effect on HR that lasts for at least 12 h with peak serum concentrations and HR-lowering effects observed one to 2 h after administration.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed that atenolol induces a time-dependent effect on HR that lasts for at least 12 h with peak serum concentrations and HR-lowering effects observed one to 2 h after administration. 35,36 This led to the conclusion that atenolol should be administered twice daily for effective HR control in cats. Our study revealed a similar effect of ivabradine on mean HR in healthy cats with a slightly different peak effect, but a comparable duration of action.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the heart rate-lowering actions of ivabradine were similar to those of atenolol, a drug commonly used in cats with hypertrophic cardiomyopathy. MacGregor et al (2008) and Quiñ ones et al (1996) evaluated the pharmacokinetic and pharmacodynamic effects of orally administered atenolol on heart rate in healthy cats. Our results revealed a similar effect of ivabradine on mean heart rate in healthy cats with a slightly different peak effect, but a comparable duration of action thereby encouraging the oral use of ivabradine in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%